From Hybrid Entrepreneurs to Entrepreneurial Billionaires: Observations on the Socioeconomic Heterogeneity of Self-employment. (February 2019) - Bögenhold, Dieter
Conventional discourses about self-employment are unsatisfactory since there is no clear acknowledgment of its heterogeneity. Interpretations tend to refer to an average type that does not exist in practice, and there are problems of coherence, demarcations, and overlap. Examining macro-level patterns of self-employment, a number of patterns emerge. First, self-employment includes both marginal and privileged positions, within individual countries and also in international comparisons. It can put people at risk of precariousness and poverty or it can be a vehicle to bring wealth to individuals and enterprises, contributing jobs and economic growth to society. Second, people increasingly switch between wage- or salary-dependent labor and self-employment and hybrid forms of employment, as forms of micro entrepreneurship are combined with dependent labor. Third, internationally, the ratio of women in solo self-employment is higher than that of men. Fourth, remarkable differences exist at the level of solo self-employment.